In-depth study of path loss and coverage areas of selected GSM signals over a typical Sudan Savannah environment - Abe, Bolanle T.; Akinbolati, Akinsanmi (Edelweiss Applied Science and Technology, 2025)
Studies on path loss and coverage areas are essential in GSM technology to ensure Quality of Service (QoS). This research was conducted on MTN and 9-Mobile 4G signals over Zaria City, Nigeria, using the COST-231 model. The measurement campaign was conducted using a drive test; Line of Sight (LOS) from the Transmitting Base Station(s) (TBS), Received Signal Strengths (RSS), elevation, longitude, and latitudes of data points were recorded. Data were collected at 100 m intervals along two routes from the TBS up to 1 km and then at 1 km intervals up to 5 km. The Spectrum Analyzer was used to measure the RSS while the GPS was used to capture the geographic parameters (latitude, longitude, elevation) for the data points. Path losses for the two routes and channels were evaluated with digital maps of coverage areas generated using GIS. Other key findings show strong RSS from TBS until about 4.0 km for both signals; beyond this range, RSS reduces drastically, approaching the sensitivity value. For GSM 4G, an Inter-TBS link of around 4 km is suggested for the study area and any similar city to improve QoS. Furthermore, a strong negative correlation coefficient (R) of -0.83 (mean value) exists between path loss and RSS, while a low R of -0.09 exists between it and elevation. A low level of signal enhancement by elevation is observed with R of +0.06 between it and RSS, and a low negative R of -0.09 between elevation and path loss. The COST-231 was optimized by generating a modified model (ZCOST-231) that incorporates some of the location-based transmission parameters. The optimized model presents valuable applications in the accurate prediction of path losses for GSM 3&4 G channels and Radio Link Design (RLD) over the study areas or any similar Sudan Savannah environment of Africa. The overall findings will significantly benefit radio link appraisal of existing GSM channels, power budgeting, and coverage area assessment in a typical Sudan Savannah City of Africa.